Studi Keanekaragaman Makrozoobentos Pada Ekosistem Perairan Lotik Di Kabupaten Jombang, Jawa Timur - Anggun Wulandari; Yurin Yuantina (Exact Papers in Compilation (EPiC), 2025)
This research aims to determine the results of identifying macrozoobenthos diversity, the results of measuring abiotic factors and the index of macrozoobenthos diversity in the lotic aquatic ecosystem in Jati Wates Village, Tembelang District and Gumulan Village, Kesamben District, Jombang Regency, East Java—research using purposive sampling technique at 3 stations with repetition 3 times. The total species found in the lotic aquatic ecosystem were 13 species consisting of Pomacea speciosa, Brotia costula, Tarebia granifera, Macrobrachium formosense, Notonectidae, Tryonia clathrata, Lymnaeidae, Rabbit Snail, Dytiscus marginalis, Margaritiferidae, Achatina fulica, Pilsbryoconcha exilis and Parathelphusa convexa, with the dominant species from the Phylum Mollusca, namely Tarebia granifera. Abiotic factors in the station 1 lotic water ecosystem have an average temperature of 26°C and an average pH of 8.5; station 2 has an average temperature of 27.5°C and an average pH of 8.5; while station 3 has an average temperature of 28.6°C and an average pH of 8.2. The diversity index (H') of macrozoobenthos in lotic aquatic based on the Shannon Weinner formula shows the diversity index from station 1, namely 1.16; station 2, namely 1.61; and station 3, namely 1.40; so that the diversity index in the lotic aquatic ecosystem is categorized as moderate.